2017
DOI: 10.1039/c7cp00284j
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of van der Waals inclusive density functional theory methods for layered electroactive materials

Abstract: Computational-driven materials discovery requires efficient and accurate methods. Density functional theory (DFT) meets these two requirements for many classes of materials. However, DFT-based methods have limitations. One significant shortcoming is the inadequate treatment of weak van der Waals (vdW) interactions, which are crucial for layered materials. Here we assess the performance of various vdW-inclusive DFT approaches for predicting the structure and voltage of layered electroactive materials for Li-ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 74 publications
1
42
0
Order By: Relevance
“…The importance of FeO 6 distortion and softening is further supported by comparing the flat structure with the corresponding rippled one, where the distortions of FeO 6 octahedrons are strongly enhanced with rippling (Figure S4e,f, Supporting Information). Note that several Van der Waals correction methods suggested for the calculation of Na deficit structures were also applied in all our calculations with qualitatively similar results (Figure S4, Supporting Information). Interestingly, we find that these Fe x TM 1− x O 2 structures can actually be DFT relaxed to all sorts of variants with different local bending geometries, as illustrated in Figure S5 (Supporting Information), with very small energy variance that is much smaller than the energy difference from the flat structure (Figure S5d, Supporting Information).…”
Section: Resultssupporting
confidence: 66%
“…The importance of FeO 6 distortion and softening is further supported by comparing the flat structure with the corresponding rippled one, where the distortions of FeO 6 octahedrons are strongly enhanced with rippling (Figure S4e,f, Supporting Information). Note that several Van der Waals correction methods suggested for the calculation of Na deficit structures were also applied in all our calculations with qualitatively similar results (Figure S4, Supporting Information). Interestingly, we find that these Fe x TM 1− x O 2 structures can actually be DFT relaxed to all sorts of variants with different local bending geometries, as illustrated in Figure S5 (Supporting Information), with very small energy variance that is much smaller than the energy difference from the flat structure (Figure S5d, Supporting Information).…”
Section: Resultssupporting
confidence: 66%
“…g ., refs 50 and 51). Therefore, we used the vdW-inclusive DFT-D3 method with a Becke-Johnson damping function (DFT-D3BJ) 52 , which has shown good accuracy to describe vdW layered electroactive materials as compared with other vdW-inclusive approaches 53 , to test the effect of vdW forces on our computed activation energies. We found that the impact of vdW forces is negligible in Si 24 , with energy differences less than 2 meV between PBE and D3BJ.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“…Carbon-based materials are at present the most commonly used negative electrode in LIBs. There are many studies on the structure of carbon atoms layer [1][2][3], and lithium adsorption in carbon-based materials [4][5][6][7][8].…”
Section: ⅰ Introductionmentioning
confidence: 99%